2021
DOI: 10.3390/life11020084
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Mechanisms of Endocytosis in Toxoplasma gondii

Abstract: Eukaryotes critically rely on endocytosis of autologous and heterologous material to maintain homeostasis and to proliferate. Although mechanisms of endocytosis have been extensively identified in mammalian and plant systems along with model systems including budding yeast, relatively little is known about endocytosis in protozoan parasites including those belonging to the phylum Apicomplexa. Whereas it has been long established that the apicomplexan agents of malaria (Plasmodium spp.) internalize and degrade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 128 publications
0
22
0
Order By: Relevance
“…gondii is capable of internalizing host-derived cytosolic proteins [ 3 ]. Once endocytosed, the material is trafficked throughout the endolysosomal system of the parasite and delivered to its lysosomal vacuolar-like compartment (VAC) for degradation by the cysteine protease cathepsin L (TgCPL) [ 4 , 5 ]. However, the molecular mechanisms by which this material is trafficked across the PV membrane (PVM) and is further endocytosed by the parasite remained poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…gondii is capable of internalizing host-derived cytosolic proteins [ 3 ]. Once endocytosed, the material is trafficked throughout the endolysosomal system of the parasite and delivered to its lysosomal vacuolar-like compartment (VAC) for degradation by the cysteine protease cathepsin L (TgCPL) [ 4 , 5 ]. However, the molecular mechanisms by which this material is trafficked across the PV membrane (PVM) and is further endocytosed by the parasite remained poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Different from the cytostome of P. falciparum, T. gondii apparently does not internalize the PV membrane by the micropore [98]. This observation was contradicted by recent studies [99][100][101], in which it has been shown that the micropore can pinch off the PV membrane. Furthermore, it was proposed that T. gondii exploits a trogocytosislike pathway to engulf host Rab small GTPases-marked Golgi or Golgi-associated vesicles, which T. gondii closely resides to, in order to gain sphingolipids [102,103].…”
Section: Toxoplasma Gondiimentioning
confidence: 74%
“…The association with the AP-2 adaptor complex, EPS15/intersectin-1-like proteins, and DrpC could also suggest a role in endocytosis at this site. Endocytosis is still poorly understood in T. gondii , but it is believed to occur at a structure called the micropore ( 26 , 34 ). The IMC suture puncta seem likely to correlate with the micropore, but additional experiments will be necessary to confirm this and a direct role in endocytosis at this site.…”
Section: Discussionmentioning
confidence: 99%